Long-term outcome of a modified balloon dilatation in the treatment of patients with achalasia - Doder Radoje; Perišić Nenad; Tomašević Ratko; Mirković Darko; Janković Zoran; Đorđević Zoran (Vojnosanitetski Pregled)
Background/Aim. Balloon dilatation is a standard approach to the initial achalasia treatment. Modified dilatation is also applied to rise efficacy and to lower complications. Methods. A total of 57 patients were analysed within a median follow-up of 8.2 years. No premedication was used, dilatation was performed up to the pain treshold, while introduction and positioning of a dilatator was done in combination of endoscopic and radiological control. Dilatation effect was estimated by both Kim Symptom Scoring and objective parameters: body weight rise and radiological scintigraphic findings. Results. Excellent and good results were obtained in 50 (88%) of the patients, while in 7 (12%) of the patients surgery was performed. There was no difference in dilatation efficacy regarding sex of the patients, but the results were better in the patients above 40 years. Duration of symptoms, body weight loss, esophageal lumen width do not indicate the definitive dilatation outcome. Esophageal scintigraphy and body weight increase were in a direct correlation with the effect of dilatation measured with the Kim Symptom Scoring. After the one to two repeated dilatations the efficacy increased from 74% to 88% justifying the repetition of dilatation. In 2 (3.57%) of the patients, that is in 2.65% of the totally dilated patients, perforation was recorded. There was no lethal outcome of dilatation, and the other complications were not clinically significant. Conclusion. Modified balloon dilatation can be recommended for initial method in achalasia treatment due to high efficacy, easy performance in daily hospital while complications are in standard range.